Common carotid to vertebral artery bypass to facilitate endovascular treatment of a basilar artery aneurysm. Issue 1 (31st January 2021) - Senanayake, Tharindu; Kader, Imran; Miteff, Ferdinand; Deshpande, Arvind
Abstract: Large posterior circulation intracranial aneurysms have a high risk of significant morbidity or mortality if left unmanaged. Endovascular techniques are well established as primary treatment for such aneurysms. This includes placement of endovascular flow diversion stents that result in progressive thrombosis and resolution of aneurysms. Successful stent placement is reliant on suitable cervical vascular access. We report a case of a 60-year-old male without direct vertebral artery access to a fusiform basilar artery aneurysm. Successful endovascular treatment required a novel hybrid technique utilizing a right common carotid to V3 segment vertebral arterial bypass to gain endovascular access to the aneurysm.